A case of in-streaming-learning: how to program with Z-tree software to design experiments on economic decision making - Nuria Hernández-León (Eduser, 2019)
In this paper, we present a real in-streaming case of learning about how to program with the z-tree software to design experiments on economic decision making for the members of the NECE Research Unit in Business Sciences, in Portugal.This real case of in-streaming-learning was created to respond the need of a teaching method based on new technologies for people who could be in different parts of the world and with different time availability, but they also need to learn to program z-tree to use it in their experiments.Researchers and students learned the Ztree software applications in business research and economic decision making. Specifically, they learned:What is z-Tree software?; What is z-Tree software for?; What advantages does it have? and What applications can you obtain in business research?; How to get it for free?; Technical requirements; The structure of z-Tree software, and How is it to be programmed?; Then, we exposed a practical example for how to create a small experiment of economic decision-making, and, finally other more complex example (with interaction between experimental subjects).This learning has been valued positively, as very useful.The paper includes the web with the training in streaming on z-Tree.